2003
DOI: 10.1016/s0195-668x(03)00195-7
|View full text |Cite
|
Sign up to set email alerts
|

The ajmaline challenge in Brugada syndrome: Diagnostic impact, safety, and recommended protocol

Abstract: The ajmaline challenge using a protocol with fractionated drug administration is a safe method to diagnose BS. Because of the potential induction of VT, it should be performed under continuous medical surveillance with advanced life-support facilities. Due to the prognostic importance all patients with aborted sudden death or unexplained syncope without demonstrable structural heart disease and family members of affected individuals should presently undergo drug testing for unmasking BS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(88 citation statements)
references
References 26 publications
4
76
0
7
Order By: Relevance
“…The intravenous administration of the sodium channel blocker ajmaline (1 mg/kg) provoked an increased STsegment elevation in the right precordial leads in all patients (positive ajmaline test). 15 Investigations during screening included noninvasive (echocardiography, stress, and rest ECGs) as well as invasive (coronary angiography, electrophysiological study, endomyocardial biopsy) techniques. 16 All patients underwent programmed electrical stimulation as reported previously.…”
Section: Patientsmentioning
confidence: 99%
“…The intravenous administration of the sodium channel blocker ajmaline (1 mg/kg) provoked an increased STsegment elevation in the right precordial leads in all patients (positive ajmaline test). 15 Investigations during screening included noninvasive (echocardiography, stress, and rest ECGs) as well as invasive (coronary angiography, electrophysiological study, endomyocardial biopsy) techniques. 16 All patients underwent programmed electrical stimulation as reported previously.…”
Section: Patientsmentioning
confidence: 99%
“…Previous studies showed that an SCB test induced VTAs in 0% to 25% of patients and VF in up to 4% of patients with BrS 13, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34. The incidence of SCB‐induced VTAs increased if the subjects of the study included subjects with spontaneous type 1 ECG.…”
Section: Discussionmentioning
confidence: 94%
“…An SCB test is useful and safe for most patients, but some studies have shown that some patients develop severe VTAs requiring external defibrillation, implantable cardioverter‐defibrillator therapy, or an extracorporeal membrane oxygenator 6, 13, 15, 19, 23, 28, 31, 34. An SCB test should be performed during hospitalization, and continuous infusion of low‐dose isoproterenol after the test should be performed overnight for high‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 If no spontaneous type I morphology was seen on the electrocardiogram (ECG), a standardized Ajmaline Challenge Test was performed conforming to current guidelines to unmask any concealed forms of BS. 20 In case of established BS, SCN5A genetic analysis was performed, according to the recommendations from the Heart Rhythm Society/European Heart Rhythm Association. 21 SCN5A variant detection in genomic DNA was carried out via high-resolution melting-curve analysis (HRMCA), followed by direct bidirectional Sanger sequencing analysis of aberrant HRMCA melting patterns and of exons and flanking intron regions for which HRMCA was not available.…”
Section: First Case/index Familymentioning
confidence: 99%